Good Antenatal Care On Mother With Multiple Endocrine Disease And Superimposed Pre Eclampsia: A Case Report - Ulfa, Mira (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Maternal pregnancy with endocrine and metabolic diseases must be planned very carefully. Hyperthyroidism was found to be 0.1-0.4% in pregnancy and many were caused by Grave's disease (85%). Diabetes mellitus is a medical complication that often occurs during pregnancy with an incidence of 3-5% of all pregnancies. Increased mortality and perinatal morbidity rates in pregnancies with diabetes mellitus are directly correlated with hyperglycemic conditions in women. Hypertension is thought to be a complication of around 7-10% of all pregnancies. Thus, awareness of antenatal care is good for pregnant women so that fewer impacts on maternal and fetal morbidity can be prevented. In this paper discuss about Mrs. RED a 34-year-old patient from polyclinic with 37 weeks gestational age. The patient knows himself with a history of hyperthyroidism, type II DM and chronic hypertension since the last 2 years. Patients are routinely do antenatal care at the Zainoel Abdidin Hospital since the beginning of gestational age because she was aware about the risk of the disease and got therapy for hyperthyroidism, diabetes mellitus and hypertension. Furthermore, in term pregnancy, the patient is planned for elective caesarean section and was born female baby bodyweight 4000 grams, with APGAR SCORE 8/9. It is proven in these patients that good antenatal care during pregnancy, especially in patients with various endocrine and metabolic diseases can reduce mortality and morbidity of mothers and babies. Poor glycemic control will cause macrosomia and will increase the risk of intra uterine fetal death. Uncontrolled hypertension main risk factor for the occurrence of eclampsia, and hyperthyroidism with excessive treatment will cause hypothyroidism in the fetus. Therefore, proper therapy is needed, so that complications for the mother and baby can be prevented.